Activation of Histone Deacetylase 2 by Inducible Heat Shock Protein 70 in Cardiac Hypertrophy - Hae Jin Kee; Gwang Hyeon Eom; Hosouk Joung; Sera Shin; Ju‐Ryoung Kim; Young Kuk Cho; Nakwon Choe; Bo‐Woong Sim; Daewoong Jo; Myung Ho Jeong; Kyung Keun Kim; Jeong-Sun Seo; et al. (2008)
Diverse cardiac diseases induce cardiac hypertrophy, which leads to dilatation and heart failure. We previously reported that hypertrophy can be blocked by class I histone deacetylase (HDAC) inhibitor, which prompted us to investigate the regulatory mechanism of class I HDACs. Cardiac hypertrophy was introduced by aortic banding, by infusion of isoproterenol or angiotensin II, or by swimming. Hypertrophic stimuli transiently elevated the activity of histone deacetylase-2 (Hdac2), a class I HDAC. In cardiomyocytes, forced expression of Hdac2 simulated hypertrophy in an Akt-dependent manner, whereas enzymatically inert Hdac2 H141A failed to do so. Hypertrophic stimuli induced the expression of heat shock protein (Hsp)70. The induced Hsp70 physically associated with and activated Hdac2. Hsp70 overexpression produced a hypertrophic phenotype, which was blocked either by siHdac2 or by a dominant negative Hsp70ΔABD. In Hsp70.1 −/− mice, cardiac hypertrophy and Hdac2 activation were significantly blunted. Heat shock either to cardiomyocytes or to mice activated Hdac2 and induced hypertrophy. However, heat shock-induced Hdac2 activation was blunted in the cardiomyocytes isolated from Hsp70.1 −/− mice. These results suggest that the induction of Hsp70 in response to diverse hypertrophic stresses and the ensuing activation of HDAC2 trigger cardiac hypertrophy, emphasizing HSP70/HDAC2 as a novel mechanism regulating hypertrophy.